2011
DOI: 10.1099/jmm.0.019703-0
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas aeruginosa fosfomycin resistance mechanisms affect non-inherited fluoroquinolone tolerance

Abstract: Pseudomonas aeruginosa is an opportunistic pathogen that poses a threat in clinical settings due to its intrinsic and acquired resistance to a wide spectrum of antibiotics. Additionally, the presence of a subpopulation of cells surviving high concentrations of antibiotics, called persisters, makes it virtually impossible to eradicate a chronic infection. The mechanism underlying persistence is still unclear, partly due to the fact that it is a non-inherited phenotype. Based on our findings from a previously pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 54 publications
0
22
0
1
Order By: Relevance
“…Moker and colleagues found that pyocanin, paraquot and the acyl-homoserine lactone 3-OC12-HSL slightly increased persister formation in exponentially growing cutlures of P. aeruginosa, but not in E. coli or S. aureus cultures [100]. De Groote et al discovered that strains with fosfomycin resistance correlated with decreased tolerance to fluoroquinolones [101]. The reasons for this correlation are still unclear, but a simple assumption is that fosfomycin resistance has a fitness cost on cells that affects susceptibility or tolerance to other antibiotics.…”
Section: Persister Formation In P Aeruginosamentioning
confidence: 99%
“…Moker and colleagues found that pyocanin, paraquot and the acyl-homoserine lactone 3-OC12-HSL slightly increased persister formation in exponentially growing cutlures of P. aeruginosa, but not in E. coli or S. aureus cultures [100]. De Groote et al discovered that strains with fosfomycin resistance correlated with decreased tolerance to fluoroquinolones [101]. The reasons for this correlation are still unclear, but a simple assumption is that fosfomycin resistance has a fitness cost on cells that affects susceptibility or tolerance to other antibiotics.…”
Section: Persister Formation In P Aeruginosamentioning
confidence: 99%
“…Surprisingly then, a recent study revealed the involvement of antibiotic resistance mechanisms in persistence. Knockout mutations of fosA and glpT, both resulting in increased resistance against fosfomycin, gave rise to decreased persistence (De Groote et al, 2011). GlpT was originally identified as a glycerol-3-phosphate (G3P) transporter in E. coli, but is also able to transport glycerol 2-phosphate (G2P) and fosfomycin into the bacterial cell, illustrating its relatively low substrate specificity (Law et al, 2009).…”
Section: Antibiotic Resistance Mechanismsmentioning
confidence: 99%
“…It would seem critically important to study the conditions under which fosA is expressed in P. aeruginosa, to ascertain what its effect is on basal MICs and whether sufficient expression to yield a resistant phenotype can be achieved by mutation or induction. One reference (De Groote et al 2011) notes that fosfomycin resistance in P. aeruginosa can be caused by (engineered) overexpression of the resident FosA because of an inserted promoter. Whether turn-on of FosA in P. aeruginosa is a possible source of mutational resistance is not known.…”
Section: Fosfomycin-modifying Enzymesmentioning
confidence: 99%